Plasma levels of soluble endothelial cell protein C receptor in patients with Wegener’s granulomatosis - BOOMSMA, M M (Blackwell Science Inc, 2002)
Elevated soluble thrombomodulin (sTM) levels are an accepted marker of endothelial damage. The physiological significance of plasma endothelial protein C receptor (sEPCR) levels is not known. To assess the relevance of this plasma protein in Wegener’s granulomatosis (WG), sEPCR levels were measured in sera obtained from WG patients and related to disease activity, sTM levels, and other known markers of disease activity. In total, 129 sera (37 at active disease, 92 during follow-up) from 31 WG patients were tested. During active disease, eight (22%) and 17 (46%) out of 37 active sera had elevated levels of sEPCR and sTM, respectively (NS); sEPCR (r = 0·39; P = 0·02) and sTM (r = 0·53; P < 0·01) levels correlated with disease activity (Birmingham Vasculitis Activity Score). Analysis of longitudinal sera revealed a significant increase in sEPCR (P = 0·01) and sTM (P = 0·04) levels prior to the moment of a relapse. Corrected for renal function, the increase in sEPCR remained significant (P = 0·04) whereas sTM did not (NS). Levels of sEPCR correlated with sTM levels (r = 0·32; P < 0·001). Plasma levels of sEPCR respond to changes in the disease in patients with WG